A new anophthalmic trechine genus and two new species from southern Guizhou, China (Coleoptera: Carabidae: Trechini) - Tian, Mingyi; Chen, Mengzhen; Ma, Zijun (Zootaxa, 2020)
A new genus and two new species of cavernicolous trechine beetles are reported from southern Guizhou Province, Southwest China: Miaotrechus mahua n. gen., n. sp. from the cave Miaoting, Getuhe cave system, Ziyun Miao & Buyi Zizhi Xian (Autonomous County), Anshun Shi; M. heweii n. sp. from the cave Jingua Dong, danzhai County, Qiandongnan Miao & Dong Zizhizhou (Autonomous Prefecture). Miaotrechus might be related to the genus Guizhaphaenops Vigna Taglianti, 1997, but it is an Anophthalmus-like, whereas Guizhaphaenops species are semi-aphaenopsian.